GJB2 and GJB6 gene transcripts in the human cochlea: A study using RNAscope, confocal, and super-resolution structured illumination microscopy - Liu, Wei; Rask-Andersen, Helge (Frontiers in Molecular Neuroscience, 2022)
Background: Gap junction (GJ) proteins, connexin26 and 30, are highly prevalent in the human cochlea, where they are involved in transcellular signaling, metabolic supply, and fluid homeostasis. Their genes, GJB2 and GJB6, are located at the DFNB1 locus on chromosome 13q12. Mutations in GJB2 may cause mild to profound non-syndromic deafness. Here, we analyzed the various expressions of GJB2 and GJB6 gene transcripts in the different cell networks in the HC using the RNAscope technique. Material and Methods: Archival paraformaldehyde-fixed sections of surgically obtained HC were used to label single mRNA oligonucleotides using the sensitive multiplex RNAscope® technique with fluorescent-tagged probes. Positive and negative controls also included the localization of ATP1A1, ATP1A2, and KCNJ10 gene transcripts in order to validate the specificity of labeling. Results: Confocal and super-resolution structured illumination microscopy (SR-SIM) detected single gene transcripts as brightly stained puncta. The GJB2 and GJB6 gene transcripts were distributed in the epithelial and connective tissue systems in all three cochlear turns. The largest number of GJB2 and GJB6 gene transcripts was in the outer sulcus, spiral ligament, and stria vascularis (SV). Oligonucleotides were present in the supporting cells of the organ of Corti (OC), spiral limbus fibrocytes, and the floor of the scala vestibuli. Multiplex gene data suggest that cells in the cochlear lateral wall contain either GJB2 or GJB6 gene transcripts or both. T0he GJB6, but not GJB2, gene transcripts were found in the intermediate cells but none were found in the marginal cells. There were no GJB2 or GJB6 gene transcripts found in the type III fibrocytes and spiral ganglion cells. Conclusion: Both GJB2 and GJB6 mRNA gene transcripts were localized in cells in the adult HC using RNAscope® in-situ hybridization (ISH) and high resolution microscopy. Generally, GJB6 dominated over GJB2, except in the basal cells. Results suggest that cells may contain either GJB2 or GJB6 gene transcripts or both. This may be consistent with specialized GJ plaques having separate channel permeability and gating properties. A reduction in the number of GJB2 gene transcripts was found in the basal turn. Such information may be useful for future gene therapy.